2014
DOI: 10.1021/np500521v
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Structural Characteristics of Schisandra chinensis Lignans Involved in P-Glycoprotein Inhibition

Abstract: The aim of the present study was to determine the structural requirements for dibenzocyclooctadiene lignans essential for P-glycoprotein inhibition. Altogether 15 structurally related lignans isolated from Schisandra chinensis or prepared by modification of their backbone were investigated, including three pairs of enantiomers. P-Glycoprotein inhibition was quantified using a doxorubicin accumulation assay in human promyelotic leukemia HL60/MDR cells overexpressing P-glycoprotein. A preliminary quantitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Curcumin is also reported to increase the Rh123 accumulation and inhibit the function of P-gp ATPase activity in KB-V1 cells [21]. The pervious findings also support the present investigation, which indicated a high accumulation of doxorubicin within HL60/MDR cells treated with Schisandra chinensis lignans [22] and natural lignans from Arctium lappa seeds, namely arctigenin, matairesinol and, arctiin can increase the retention of the P-gp substrate Rh123 in CEM/ADR cells, indicating that these lignans can inhibit the activity of P-gp and, other ABC transporters [23]. …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Curcumin is also reported to increase the Rh123 accumulation and inhibit the function of P-gp ATPase activity in KB-V1 cells [21]. The pervious findings also support the present investigation, which indicated a high accumulation of doxorubicin within HL60/MDR cells treated with Schisandra chinensis lignans [22] and natural lignans from Arctium lappa seeds, namely arctigenin, matairesinol and, arctiin can increase the retention of the P-gp substrate Rh123 in CEM/ADR cells, indicating that these lignans can inhibit the activity of P-gp and, other ABC transporters [23]. …”
Section: Discussionsupporting
confidence: 86%
“…Since the cell cycle arrest in the G2/M phase is usually a cellular response to PTX treatment, it can be assumed that GLU potentiate the effect of PTX in resistant KB cells. A previous report has suggested that S. chinensis lignans in combination with doxorubicin significantly increased the proportion of G2/M phase in HL60/MDR cells [22]. Docetaxel is a microtubule inhibitor affecting the S and G2/M phases of the cell cycle [25].…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer action of lignans was also connected with P-glycoprotein inhibition. Some dibenzocyclooctadiene lignans possess three main structural features involved in P-glycoprotein inhibition: a 1,2,3-trimethoxy moiety, a 6-acyloxy group, and the absence of a 7-hydroxy group (Slanina et al 2014). The most effective anticancer properties based on structure–activity relationships studies were shown for gomisin N and deoxyschisandrin (Gnabrea et al 2010; Slanina et al 2014).…”
Section: Structure–activity Relationships Of Lignansmentioning
confidence: 99%
“…Modern studies have determined that S. chinensis extract (SCE) is composed of polyphenols, flavonoids, essential oils, and polysaccharides (Wang et al, ; Huyke et al, ). It has been reported that SCE is antiinflammatory (Song et al, ), antibacterial (Zhang et al, ), antiproliferative (Zhang et al, ), anticancer (Slanina et al, ), free radical scavenging (Wang et al, ; Huyke et al, ), and protective against UVB‐induced DNA damage (Hou et al, ). Essential oil purified from S. chinensis were screened for antibacterial activity against both Gram‐positive ( Staphylococcus epidermidis , S. aureus , and Bacillus subtilis ) and Gram‐negative ( Escherichia coli , Pseudomonas aeruginosa , and Proteus vulgaris ) bacteria (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%